Monstros, antipetismo e o enquadramento de Lula nas capas da revista veja (2002-2020) - Machado, Ariane Cristina (Universidade Federal de São Carlos, 2022)
This research aims analyze how the Mainstream Media uses certain marks of meaning, and relates them to different cultural substrates. Thus, it is part of an already traditional debate in the field of Political Communication, which since the 90s has investigated the relationship between Political Journalism and its role in the construction of representations about politics and politicians. In this sense, we seek to answer the following question: how did Veja Magazine frame Lula as a monster on its covers between 2002 and 2020? Based on the notion of framing operationalized by Content Analysis, we seek to relate the dimensions of monstrosity and anti-PTism, based on the greatest PT political leadership today. For this, we built an analysis corpus that contains magazine covers from 2002 to 2020, that is, between the first presidential election and Lula's release from prison, years in which the PT member was in greater media prominence since the beginning of his political career. The results showed different types of monsters built around the figure of the former president, reinforcing the historical liberal-conservative alignment of the Brazilian press.
Monsters, antipetism and Lula’s framing on the covers of veja magazine (2002-2020)
Keywords: Lula; Jornalismo político; Political journalism; Antipetismo; Antipetism; MAXQDA; Revista Veja; Veja Magazine; Monstros; Monsters; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO